POLITIQUE DE RECRUTEMENT DES NOUVELLES UNITES DANS UNE INSTITUTION DE L’ENSEIGNEMENT SUPERIEUR ET UNIVERSITAIRE - Moustapha, GENDANU TEREMBI; ANIBILONI SUNGUFUE Brigitte, (IJRDO- Journal of Educational Research, 2020)
The survey is about the recruiting politics of new units in an institution of the higher education and academic, case of the ISC/Kisangani of 2012 to 2017.Our survey sets like objectives to value the recruiting politics of the new units. Concretely, it about of :To determine if recruiting politics of the new units corresponds to the criteriaas of engagement of the staff within the ESU ;To show if they are satisfactory, that is to say to the doorstep superior or equal to 50%.The recruitment within establishments of the ESU is guaranteed by the academic instructions in force, but today following the mutations observed in the chief of the politicians, the sector of the ESU displayed of the antivaleurs without names whose ISC/Kisangani is not saved. The staff’s recruitment doesn’t respect the procedures in force insofar as Rectors and General Managers receive some recommendations without holding account of the criterias of eligibility and the setting and organic structure.